PENDEKATAN KONSTRUKTIVISTIK DAN PENGEMBANGAN BAHAN AJAR PADA SISTEM PENDIDIKAN JARAK JAUH - Benny A Pribadi; Edy Sjarif (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2010)
Distance learning university has unique characteristics. One of them is the amount of student which is usually larger than the conventional university. In order to serve its students better, both academic and administrative, the distance learning university usually applies a uniform approach in designing students learning activities. The approach covers learning process and examination components. The reason of using this approach is mainly based on managerial factors. The uniform approach which is associated with behavioral learning theory limit the creativity of distance students to construct their knowledge. It is necessary for the distance learning students to have a broad spectrum of knowledge used in daily professional activities. The purpose of the present paper is to elaborate the possibilities of using other approaches that will be able to enhance student knowledge. Instead of using uniform or behavioral approach, there are possibilities to apply a constructivism theory in printed learning material to be used distance learning system.